Mekanisme Respon Tanaman Padi terhadap Cekaman Kekeringan dan Varietas Toleran - Sujinah Sujinah; Ali Jamil (Iptek Tanaman Pangan, 2016)
Drought has wide impact on agriculture such as reduced rice productivity and production, impacted on food security and economical stability in the region as well as at national level. Drought stress problem would become more frequent in relation with accelerated global climate changes. Response of rice crop to water stress begins with physiological process disturbance in the plant, such as reducing transpiration rate by means of stomata closure and reducing leaf surface area or leaf rolling. Each action may cause reducing CO2 and O2 gas exchanges to the atmosphere, and reduce solar radiation interception. Both condition may decrease photosynthetic process on the leaves. This physiological responses may affect plant morphology such as reducing canopy size due to decreasing leaf number and leaf area per hill, reducing number of total and productive tillers per hill, delaying flowering and grain maturing. Changes in this crop morphology also have impact on further crop physiological processes. Therefore, there are inter-affects between physiological processes and crop morphology. The changes of the processes and condition cause the changes of crop growth pattern, and finally decrease biomass weight, yield components and grain yield. The degree of declining depending on the drought stress level and also on the rice genotype which have different adaptability and tolerance mechanism to drought stress.